STRATEGI VISUAL KEMASAN MARKET LEADER MIE INSTAN DI INDONESIA - Robert Hendra Yudianto; Adnan Setyoko (Pusat Riset dan Inovasi Nasional, 2022)
Packaging has multiple roles that greatly affect the target audience and even the target market. Not only does it play a role in protecting or facilitating distribution, far from that, packaging can communicate many aspects at the same time even in the absence of sales. Packaging deserves special attention and is done optimally as an effective communication medium. This study tries to describe the visual strategy on instant noodle packaging which is the market leader in Indonesia, namely Indomie. Indomie As the only brand that is able to dominate 70% of the market compared to its closest competitor, only 16%. Although not the only major factor, there are many interesting things that we can describe from the visual strategy that has been implemented by Indomie producers in competing with similar products. This research was conducted using descriptive qualitative methods to determine the visual strategy by outlining the graphic elements of the packaging. The results of this study indicate that a strong visual identity is able to influence consumers to more quickly recognize their products and at the same time conduct persuasion to choose their products in the ranks of other similar products.